Hepatoprotective Effect of Aqueous and N-Hexane Extract of Nigella Sativa in Paracetamol (Acetaminophen) Induced Liver Diseases of Rats - A Histopathological Evaluation - Mainul, Haque; Nor Iza, A.rahman; Farida, Yesmin (2013)
Acute over dose of paracetamol (acetaminophen) causes serious hepatic necrosis. So, this study was conducted to observe the hepatoprotective activity of aqueous and n-hexane extract of Nigella sativa in paracetamol induced hepatotoxicity in rats in Dhaka, Bangladesh from 2008 to 2010. Single dose of paracetamol was administered on day one and rats were sacrificed on day three. Liver damage was evaluated by hepatic histology. Aqueous and n-hexane extract of Nigella sativa was administered orally into two other rat groups through intra-gastric tube for 28 days in which paracetamol was administered orally on day 28 and were sacrificed on day 30. Liver of all rats were excised and processed for light microscopy with a view to histopathological evaluation. The histological examination of the liver tissues in vehicle treated group and paracetamol-control group of rats showed normal hepatic architecture, centrilobular necrosis, polymorph (neutrophils) infiltration and pyknosis of the hepatocytes respectively. The hepatic architecture of rats pre-treated with aqueous extract of Nigella sativa showed improvement of necrosis with very few pyknotic nuclei when compared to the paracetamol-control group. The hepatic architecture of rats pre-treated with aqueous extract as well as with the n-hexane extract of Nigella sativa did not show pyknotic nuclei and polymorph infiltration while apparently regenerating hepatocytes, visible under the microscope. Aqueous extract and n-hexane extract of Nigella sativa extended hepatoprotection by reducing oxidative stress in experimental liver damage in rats. Furthermore, the protection afforded by the n-hexane extract of Nigella sativa pre-treated group was superior to the aqueous extract of Nigella sativa pre-treated group. Keywords: Hepatoprotective, Liver-damage, Nigella sativa Linn.